Booms and busts in China's stock market: Estimates based on fundamentals - Gabe de Bondt; Tuomas A. Peltonen; Daniel Santabárbara (European Central Bank (ECB), 2010)
This paper empirically models China's stock prices using conventional fundamentals: corporate earnings, risk-free interest rate, and a proxy for equity risk premium. It uses the estimated longrun stock price misalignments to date booms and busts, and analyses equity market reforms and excess liquidity as potential drivers of these stock price misalignments. Our results show that China's equity prices can be reasonable well modelled using fundamentals, but that various booms and busts can be identified. Policy actions, either taking the form of deposit rate changes, equity market reforms or excess liquidity, seem to have significantly contributed to these misalignments.
Keywords: G12; G18; 330; China; Equity market; liquidity; reforms; Stock price; Börsenkurs; Aktienmarkt; Finanzanalyse; Konjunktur; China